Exploring the potential of nanofluids to enhance the productivity of solar stills - Charitar, Deepti (Department of Mechanical Engineering, 2020)
Desalination technologies are being used to augment access to safe drinking water around the world. Nonetheless, most of these technologies are energy-intensive and driven by fossil fuels which emit greenhouse gases into the atmosphere, thereby contributing to climate change. Additionally, fossil fuels are non-renewable sources of energy and the exhaustion of such reserves can cause a threat to energy security. Consequently, exploitation of sustainable sources of energy for the desalination process has attracted a lot of attention. One such strategy is the use of a solar still which utilises solar energy to produce fresh water from saline or brackish water. However, the major drawback of a solar still lies in its low productivity. Many studies have investigated means of increasing the productivity of a solar still. One such technique which has recently been studied is to disperse nanoparticles into the impure water inside the basin of a solar still in order to obtain a nanofluid with enhanced optical and heat transfer characteristics. Since this is a relatively new topic, very few numerical studies on solar stills with nanofluids are available. Moreover, based on a literature review, no study examining the effect of nanoparticle size on the productivity of solar stills, and on the economic and environmental performance of solar stills was found. Additionally, the few available numerical studies on solar stills with nanofluids have not taken into account the view factor in the computation of the internal radiative heat transfer coefficient. Therefore, the aim of this study was to investigate both numerically and experimentally the effect of nanoparticle size on the performance of solar stills. Mathematical models with the view factor (Model 1) and without the view factor (Model 2) were developed for single slope solar stills, and a code was written in MATLAB software to solve a system of equations iteratively. Calculations were performed using climatic data from Stellenbosch (latitude 33.93°S, longitude 18.86°E) and University of Cape Town (latitude 33.96°S, longitude 18.46°E), South Africa, in order to evaluate the performance of solar stills with varying nanoparticle sizes. For the experimental phase, four identical solar stills were designed and built, and they were first tested with water only (base fluid) in all of them to test their performance and for calibration purposes. An Analysis of Variance (ANOVA) test was conducted on the experimental data collected from this first test. Subsequently, nanofluids containing aluminium oxide (Al2O3) nanoparticles of size 10 nm, 50 nm and 100 nm were used in three of the solar stills, with the other solar still containing the base fluid only. All the experiments were conducted at the University of Cape Town. The mathematical models were then validated using experimental data. Simulations in MATLAB based on Stellenbosch climatic data showed that for the month of January, which is a summer month in South Africa, the productivity of the solar still with the 10 nm, 50 nm and 100 nm Al2O3 nanoparticles was 9.01%, 8.94% and 8.89%, respectively higher than the productivity of the solar still with the base fluid only. On the other hand, for the month of July, which is a winter month in South Africa, the average productivity of the solar still with the 10 nm, 50 nm and 100 nm Al2O3 nanoparticles was 1.31%, 1.23% and 1.19%, respectively higher than the productivity of the solar still with base fluid only. In terms of the economic analysis, the simulations in MATLAB based on annual climatic data from Stellenbosch revealed that the cost of distilled water obtained from the solar still with the 10 nm, 50 nm and 100 nm Al2O3 nanoparticles was 10.42%, 6.21% and 3.51%, respectively higher than the cost of water obtained from the solar still with the base fluid only. Additionally, the payback period for the solar still with the 10 nm, 50 nm and 100 nm Al2O3 nanoparticles was 13.32%, 7.86% and 4.37%, respectively higher than the payback period for the solar still with the base fluid only. In terms of the environmental performance, the amount of carbon dioxide equivalent (CO2 equivalent) mitigated by the solar still with the 10 nm, 50 nm and 100 nm Al2O3 nanoparticles was 6.18%, 6.11% and 6.06%, respectively higher than the amount of CO2 equivalent mitigated by the solar still with the base fluid only. For the experimental phase, the ANOVA test based on the first set of experimental data (with base fluid only in all four solar stills) gave a probability-value (P-value) of 1.00. Moreover, experimental data collected from solar stills with base fluid and nanofluids revealed that the productivity of the solar still with nanoparticles of size 10 nm and 50 nm was 26.46% and 1.46%, respectively higher than the productivity of the solar still with base fluid only. On the other hand, the productivity of the solar still with nanoparticles of size 100 nm was 9.38% lower than that of the solar still with base fluid only. Furthermore, the root mean square error (RMSE) for the solar stills with nanofluids for Model 1 and Model 2 was 22.02% and 36.03%, respectively. It was confirmed that the performance of the calibrated solar stills was not significantly different. Moreover, the enhancement in the productivity of a solar still with nanofluids is much more distinct in summer than in winter. It was also demonstrated that the productivity of a solar still decreases with increasing nanoparticle size. Additionally, it was established that the cost of distilled water, the payback period and the amount of mitigated CO2 equivalent decrease with increasing nanoparticle size. Theoretically, the distillate yield and environmental performance of a solar still with nanofluids were marginally sensitive to the nanoparticle size while the cost of distilled water and payback period were significantly affected by the nanoparticle size. The effect of nanoparticle size on distillate yield was experimentally significant. Finally, it was demonstrated that the inclusion of the view factor improves the accuracy of modelling of solar stills with nanofluids.